2016
DOI: 10.1063/1.4953254
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-induced confinement of continuous hole-states in highly pumped, industrial-grade, green InGaN quantum wells

Abstract: We investigate industrial-grade InGaN/GaN quantum wells (QWs) emitting in the green spectral region under high, resonant pumping conditions. Consequently, an ubiquitous high energy luminescence is observed that we assign to a polarization field Confined Hole Continuum (CHC). Our finding is supported by a unique combination of experimental techniques, including transmission electron microscopy, (time-resolved) photoluminescence under various excitation conditions, and electroluminescence, which confirm an exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The TIPL and TRPL spectra shown in Figs. 1 and 4, respectively, are similar to those reported by Sun et al 16 and Nippert et al 21 . In order to investigate further the temporal behavior of the HEB, PL decay transients were measured at various detection energies across the spectrum at a peak excited carrier density of 2.2 × 10 13 cm -2 per pulse and are shown in Fig.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The TIPL and TRPL spectra shown in Figs. 1 and 4, respectively, are similar to those reported by Sun et al 16 and Nippert et al 21 . In order to investigate further the temporal behavior of the HEB, PL decay transients were measured at various detection energies across the spectrum at a peak excited carrier density of 2.2 × 10 13 cm -2 per pulse and are shown in Fig.…”
Section: Resultssupporting
confidence: 90%
“…This observation was explained as being due to the greater electron/hole wave function overlap of the delocalized holes and electrons. Central to the arguments presented by Schulz et al 20 and Nippert et al 21 is that at the high excitation carrier densities localized state saturation occurs resulting in Pauli state blocking similar to that reported in semiconductor quantum dots (QDs) [22][23][24][25][26] . Furthermore, Shahmohammadi et al 27 attributed the high energy emission band observed at high excitation densities to recombination involving an electron-hole plasma whose dynamics were dominated by Auger recombination.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Therefore, the QCSE in the whole ND series becomes negligible, resulting in the convergence of the total energy shifts against 12 meV (visible in Fig. 3) indicating an ND-band-filling effect [54][55][56] . Hence, the overall emission-peak positions of the confinement regime samples in Fig.…”
Section: Discussionmentioning
confidence: 97%